2017
DOI: 10.3329/bjp.v12i2.31238
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of Atractylodes macrocephala extract by double induction of apoptotic and autophagic cell death in head and neck cancer cells

Abstract: The apoptosis resistance restricts the efficacy of traditional therapies of head and neck squamous cell carcinoma (HNSCC). To overcome this problem, Atractylodes macrocephala, a traditional Korean and Chinese herbal medicine, has been used in clinical practice. In the present study, the anticancer effect of A. macrocephala extract was investigated and its underlying mechanisms using head and neck cancer KB cell line. The extract-induced cytotoxicity was mediated by autophagic cell death as well as apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been reported that Astragalus polysaccharide ( Li et al, 2020a ), Hericium erinaceus polysaccharide ( Liu et al, 2020 ), Angelica sinensis polysaccharide ( Yang J. et al, 2018 ) and Lentinus edodes polysaccharide ( Xu et al, 2018 ) have antitumour activity. The polysaccharides from AM showed extensive antitumour activity on many kinds of tumour cells, such as oesophagal cancer, liver cancer, malignant glioma, colorectal cancer and lung cancer cells ( Kou et al, 2017 ; Zhu et al, 2018 ). The anticancer activity is mediated via inducing tumour cell apoptosis, inhibiting tumour cell migration, invasion and metastasis, regulating the tumour microenvironment and immune function, and inhibiting tumour cell proliferation ( Chen and Huang, 2018 ) ( Table 3 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…It has been reported that Astragalus polysaccharide ( Li et al, 2020a ), Hericium erinaceus polysaccharide ( Liu et al, 2020 ), Angelica sinensis polysaccharide ( Yang J. et al, 2018 ) and Lentinus edodes polysaccharide ( Xu et al, 2018 ) have antitumour activity. The polysaccharides from AM showed extensive antitumour activity on many kinds of tumour cells, such as oesophagal cancer, liver cancer, malignant glioma, colorectal cancer and lung cancer cells ( Kou et al, 2017 ; Zhu et al, 2018 ). The anticancer activity is mediated via inducing tumour cell apoptosis, inhibiting tumour cell migration, invasion and metastasis, regulating the tumour microenvironment and immune function, and inhibiting tumour cell proliferation ( Chen and Huang, 2018 ) ( Table 3 ).…”
Section: Biological Activitiesmentioning
confidence: 99%